Stochastic models of the slow/fast type of atrioventricular nodal reentrant tachycardia and tachycardia with conduction aberration - Jackowska-Zduniak, Beata (Zielona Góra: Uniwersytet Zielonogórski)
Models are proposed to describe the hart`s action potential. A system of stochastic differential equations is used to recreate pathological behaviour in the heart such as atrioventricular nodal reentrant tachycardia (AVNRT) and also AVNRT with conduction aberration. Part of the population has abnormal accessory pathways: fast and slow. An additional pathway is not always induced, since the deterministic model is not proper due to a stochasticity in this process.
Keywords: mathematical model; stochastic differential equations; action potential; atrioventricular nodal reentrant tachycardia; conduction aberration